Frequency and its Type of Endometrial Hyperplasia Among Perimenopausal Women Presenting with Polymenorrhagia - Sara Munir, Momna Iqbal, Amber Batool, Saba Khalid (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The goals of this study were (1) to assess the prevalence of endometrial hyperplasia in perimenopausal women presenting with polymenorrhagia, and (2) to identify the prevalence of different types of endometrial hyperplasia in this population. Methodology: In this Cross Sectional survey at the Sheikh Zyed Hospital, Lahore during May 2021 to December 2021, 100 cases with > 45 years of age with symptoms of perimenopause, presenting with polymenorrhagia were included in the study. Clinical evaluation began with comprehensive history taking. Patients were extensively examined after a detailed history was taken. A complete physical, internal, and pelvic examination were performed. All patients were examined by per rectum examination. TVS was performed to check for endometrial thickness and ovarian hypertrophy. Diagnostic curettage preferably in the second half of the cycle was done in patients positive for hyperplasia and histopathology of the specimens done to determine types of hyperplasia. Results: In our study, 61%(n=61) were between 45-50 years and 39%(n=39) were between 51-55 years, mean+sd was calculated as 47.34+6.84 years, frequency of endometrial hyperplasia among perimenopausal women presenting with polymenorrhagia revealed in 21%(n=21) and among them frequency of types of endometrial hyperplasia among perimenopasual women presenting with polymenorrhagia was recorded as 15(71.43%) with Cystic type of hyperplasia, 4(19.05%) had Adonomatous hyperplasia, and 2(9.52%) had atypical hyperplasia. Conclusion: Cystic hyperplasia was the most frequent kind of hyperplasia, and we determined that the prevalence of endometrial hyperplasia among perimenopausal women presenting with polymenorrhagia was not considerably prevalent in our population than in developed countries. Keywords: Perimenopausal women, polymenorrhagia, endometrial hyperplasia, Cystic, Adonomatous, Atypical type of hyperplasia.